EKSPLORASI AKTIVITAS KEHIDUPAN SEHARI-HARI ANAK NELAYAN DI DESA LOBUK UNTUK MENDUKUNG PEMBELAJARAN IPA KONTEKSTUAL - Novatul Labibah; Herowati Herowati; Jefri Nur Hidayat; Habibi Habibi (EDUSAINS, 2020)
EXPLORATION OF FISHERMAN CHILDREN'S DAILY LIFE ACTIVITIES AT LOBUK VILLAGE TO SUPPORT CONTEXTUAL SCIENCE LEARNINGAbstractThe daily activities of fishermen's children can be used as a material context in applying contextual science learning, as emphasized by K13. In fact, learning science in coastal schools is not yet contextual to the daily activities of fishermen's children. This study aims to provide a description of the daily activities of fishermen's children in Lobuk Village, and a description of the relationship between these activities and science learning materials for SMP/MTs. This type of research is a descriptive qualitative case study method. The primary data sources were fishermen children aged SMP/MTs and their parents. Data collection techniques in the form of interviews, observation, and documentation. The results showed that fishermen's children's morning activities were helping with homework, preparing for school, then leaving for school. The daytime activity is helping the mother/aunt work in the drying process of the fish (a gherri jhuko'). The afternoon activity is looking for shells (arang-karang) during low tide, some of the shells are sold to earn pocket money or for parents, and some are used as salad. Nighttime activities are reciting/tarawih, tadarus, watching TV, then sleeping. The daily activities of fishermen children in their routine of helping to work a gherri jhuko’ and arang-karang in Lobuk Village are related to science learning materials for SMP/MTs, namely the classification of shells in Mollusca type invertebrates; the application of solid substance pressure to the knife for nyetak, mowang bunto ', and a gherri jhuko'. AbstrakAktivitas sehari-hari anak nelayan bisa digunakan sebagai konteks materi dalam menerapkan pembelajaran IPA kontekstual, sebagaimana penekanan K13. Faktanya, pembelajaran IPA di sekolah pesisir belum kontekstual terhadap aktivitas sehari-hari anak nelayan. Penelitian ini bertujuan untuk memberikan deskripsi aktivitas sehari-hari anak nelayan di Desa Lobuk, dan deskripsi keterkaitan aktivitas tersebut dengan materi pembelajaran IPA SMP/MTs. Jenis penelitian ini adalah deskriptif kualitatif dengan metode studi kasus. Sumber data primer dari anak-anak nelayan usia SMP/MTs beserta orang tua. Teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan aktivitas pagi hari anak nelayan adalah membantu pekerjaan rumah, menyiapkan diri ke sekolah, lalu berangkat sekolah. Aktivitas siang hari adalah membantu ibu/bibinya bekerja dalam proses pengeringan ikan (a gherri jhuko’). Aktivitas sore hari adalah mencari kerang (arang-karang) saat air laut surut, sebagian kerang dijual untuk menghasilkan uang jajan atau untuk orang tua, dan sebagian lagi dirujak. Aktivitas malam hari adalah mengaji/tarawih, tadarus, nonton TV, lalu tidur. Aktivitas sehari-hari anak nelayan dalam rutinitas membantu bekerja a gherri jhuko’ dan arang-karang di Desa Lobuk berkaitan dengan materi pembelajaran IPA SMP/MTs, yaitu pengklasifikasian kerang dalam avertebrata jenis Mollusca; penerapan tekanan zat padat pada pisau untuk nyetak, mowang bunto’, dan a gherri jhuko’.